The development of specifications-based S- and L-type robust designs. (1st January 2013) - Chan, Hsin-Li; Cho, Byung Rae
Chan and Cho (2013) studied the specifications-based robust design optimisation for a nominal-the-best type ( N -type) quality characteristic under the normality assumption as an underlying distribution of the characteristic. In the real life engineering environment, however, various quality characteristics are of smaller-the-better ( S -type) or larger-the-better ( L -type) and their distributions are heavily skewed. As an extension of Chan and Cho (2013), this paper proposes specifications-based robust design (RD) models for S - and L -type quality characteristics, which are constrained by pre-specified upper and lower specification limits (USL and LSL), respectively. This paper demonstrates that the Weibull distribution is effective in modelling the S - and L -type characteristics, derives the truncated mean and variance from the Weibull parameters, and incorporates those truncated statistical moments into response surface-based RD models. Finally, numerical examples illustrate how the optimal factor settings are obtained from the proposed models.